Niat Beli Ulang di Indomaret Point Kota Semarang - Suhaji, Suhaji; Maghfiroh, Maghfiroh; Purwani, Tri (STIE Widya Manggala, 2025)
This research aims to test and analyze empirically, how price, product quality and service quality have influence on consumers' repurchase intentions at Indomaret Point, Semarang City. The population in this study were all Indomaret Point consumers in the city of Semarang, with a sample size of 100 respondents, using the Cluster random sampling technique. Data was collected by distributing questionnaires, while data analysis was carried out using multiple linear regression, and processed using SPSS version 26. The results of the analysis showed that price, product quality and service quality had a significant positive effect on repurchase intentions. It means that if the price, product quality and service quality at Indomaret Point are better, then consumers'repurchase intentions will increase.